Multidisciplinary Approach in Islamic Religious Education: The Formation of a Holistic and Responsive Muslim Community to the Dynamics of Modern Life - Mohamad Muhsan; Abdul Haris (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The writing of this article aims to explore the role of a multidisciplinary approach to the formation of Muslims who are holistic and responsive to the dynamics of modern life as a content of Islamic religious education. The multidisciplinary approach blends various disciplines, including social sciences, sciences, and humanities, with Islamic religious education. This research method uses a qualitative and multidisciplinary approach that includes literature study, content analysis, and synthesis of findings from various disciplines. The literature study results concluded that a multidisciplinary approach is relevant and essential in forming Muslims who can adapt to the dynamics of modern life without losing the roots of Islamic religious values. This confirms that the integration of this approach is a strong foundation for the development of holistic, responsive, and competitive Muslims who face the complexity of the times. In addition, this approach has been proven to increase the involvement of Muslims in social and environmental issues, creating individuals who are not only religious but also contribute positively to global society. The implications of these findings can be the basis for the development of educational policies, community development programs, and holistic Muslim development strategies in the face of the complex dynamics of modern life.